Koncepcja technologii zabezpieczania wykopu dla płytko zlokalizowanych tuneli kolejowych formowanych w formach traconych - Michałek, Marian (Wydawnictwa AGH, 2009)
The conception of temporary lining for tunnel construction in open trench technology was showed here. In this case the train tunnel is constructed with prefabricated sections formed partially at a place of its localization. Section of the tunnel consists of form filled with concrete directly in the trench. The construction which make possible manipulation of the empty forms in the trench was also presented.

W artykule przedstawiono koncepcję zabezpieczania wykopu dla umożliwienia wykonywania tunelu kolejowego prefabrykowanego w miejscu lokalizacji poprzez wypełnianie form traconych wraz z zastosowaniem systemu rozparcia ścian wykopu. Przedstawiono również zarys konstrukcji ułatwiających operowanie formami traconymi w wykopach.
Conception of the temporary lining for the railroad tunnel formed in the missed forms at a place of its localization at the small depth
Górnictwo i Geoinżynieria
Bibliogr. s. 273.
Keywords: tunnelling; budownictwo tunelowe; trench stabilisation; obudowa wykopów